PRODUKSI BUBUK INOKULUM URUTAN DARI KULTUR MURNI Pediococcus acidilactici U318 DENGAN BEBERAPA JENIS BAHAN PENGISI - Semadi Antara, Nyoman; Urip Sanjaya Trisna, I P. G.; Suter, I Ketut (Agrotekno, 2009)
Aim of the research was to find out the viability ofPediococcus acidilactici U318 in inoculum powder duringstorage. The filler material used in the production ofinoculum powder was three kinds of flour, namely maizena,rice flour and tapioca. The research was done in laboratoryscale as experiment research which was designed byrandomized block design with factorial experiment. Twofactors were experimented, namely the kinds of flour as afiller material as the first factor and the storage period as thesecond factor.Result of the research showed that the treatment of flouras a filler material did not influence the viability of P.acidilactici U318 in inoculum powder. Any filler materialused in production of the powder gave same protective actionon its viability. The viability of P. acidilactici U318decreased during storage period. After storage of 4 weeks theaverage of viable P. acidilactici U318 was about 2,54x1010cfu/g which decreased one log cycle from the initial ofstorage.